2020
DOI: 10.1016/j.dsx.2020.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of new active cases of coronavirus disease (COVID-19) pandemic using multiple linear regression model

Abstract: Introduction and Aims The COVID-19 pandemic originated from the city of Wuhan of China has highly affected the health, socio-economic and financial matters of the different countries of the world. India is one of the countries which is affected by the disease and thousands of people on daily basis are getting infected. In this paper, an analysis of daily statistics of people affected by the disease are taken into account to predict the next days trend in the active cases in Odisha as well as India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(112 citation statements)
references
References 13 publications
1
83
0
3
Order By: Relevance
“…The above mixed GWR model turns to the standard GWR model when global effects can be ignored and, when local effects can be ignored, the mixed GWR model turns to the traditional multiple linear regression (MLR) model. The MLR model (e.g., Rath et al, 2020 ) assumes that the explanatory variables are spatially stationary over the whole study area, which, therefore, only provides global estimates ( Yu & Peng, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The above mixed GWR model turns to the standard GWR model when global effects can be ignored and, when local effects can be ignored, the mixed GWR model turns to the traditional multiple linear regression (MLR) model. The MLR model (e.g., Rath et al, 2020 ) assumes that the explanatory variables are spatially stationary over the whole study area, which, therefore, only provides global estimates ( Yu & Peng, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…We adopted a linear approach assuming strict exogeneity amongst the explanatory variables. A linear approach was outlined by several studies, as the literature shows the variations in COVID-19 cases deaths and cases fits a linear structural model best when regressed against various exogenous variables ( Adekunle et al, 2020 ; Nguimkeu and Tadadjeu, 2021 ; Ogundokun et al, 2020 ; Rath et al, 2020 ; Sardokie and Owusu, 2020 ). The functional relationship is expressed as: where Y iN are the dependent variables related to aggregated COVID-19 cases and deaths for the individual countries (i) for the total number of countries observed in the dataset (N) and X 1 ,X 2 ,.....,X iN are independent exogenous variables for the ith country in the total number of countries (N).…”
Section: Methodsmentioning
confidence: 99%
“…Rath [16] used Multiple Linear Regression Model to predict that the number of daily active cases in India would reach 52,290 by 15 August. Ayyoubzadeh et al [17] used Multiple Linear Regression Method to predict the spread of COVID-19 in Iran, and found that in addition to the incidence of the previous day, factors that can effectively improve the accuracy of the prediction also include hand sanitizer usage and hand washing frequency.…”
Section: Multiple Regression Analysis Models Have Been Widely Used Inmentioning
confidence: 99%